2013
DOI: 10.1063/1.4840695
|View full text |Cite
|
Sign up to set email alerts
|

Understanding tetrahedral liquids through patchy colloids

Abstract: We investigate the structural properties of a simple model for tetrahedral patchy colloids in which the patch width and the patch range can be tuned independently. For wide bond angles, a fully bonded network can be generated by standard Monte Carlo or molecular dynamics simulations of the model, providing a neat method for generating defect-free random tetrahedral networks. This offers the possibility of focusing on the role of the patch angular width on the structure of the fully bonded network. The analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 62 publications
(102 reference statements)
7
52
0
Order By: Relevance
“…We also note that there is no evidence of a pre-peak, the typical signature of tetrahedral networks. It has been recently shown that there is a clear correlation between the strength (or the presence) of the pre-peak and the variance of the center-centercenter angle θ distribution [52]. For very wide θ distributions (as in the present case) the pre-peak is expected to be missing, since there is no sufficient geometrical correlation to establish a tetrahedral network.…”
Section: Structure Factormentioning
confidence: 82%
“…We also note that there is no evidence of a pre-peak, the typical signature of tetrahedral networks. It has been recently shown that there is a clear correlation between the strength (or the presence) of the pre-peak and the variance of the center-centercenter angle θ distribution [52]. For very wide θ distributions (as in the present case) the pre-peak is expected to be missing, since there is no sufficient geometrical correlation to establish a tetrahedral network.…”
Section: Structure Factormentioning
confidence: 82%
“…Such a minimal perspective is a com mon one in statistical mechanics, and many studies have shown that simple models can be used to describe a wide range of systems (see e.g., Refs. [19][20][21] for application to tetrahedral liquids). Correspondingly, several exam ples of molecular self-assembly at surfaces can be de scribed in common physical terms.…”
Section: Rhombus Tilings From Rhombus-like Interactionsmentioning
confidence: 98%
“…Whereas at high temperatures (T = 0.14) the structure of the system is essentially that corresponding to a hard-sphere liquid with a main peak at qσ ∼ = 7, upon cooling the system we clearly see the signature of an archetypal tetrahedral structure by the emergence of an additional tetrahedral peak at qσ ∼ = 4.5. Thus, due to the judicious choice of the density and patch size, the system at low T exhibits no crystalline order but an amorphous tetrahedral network structurally similar to that present in atomistic systems such as silica or silicon [2,58], classical water models [42], or models of colloidal gels where double peak structures are imposed by means of three-body interactions [78].…”
Section: Discussionmentioning
confidence: 99%
“…Our particular realization consists of particles with four attractive patches tetrahedrally distributed on the particle surface [36,37]. Despite its simplicity, this and similar models [34,[38][39][40][41] have already shown the capability for capturing some of the fundamental structural features of different classical systems with amorphous tetrahedral structure such as atomistic models of water, silicon, or silica [2,[42][43][44]. In general, due to their highly versatile functionality, these models have not only the potential for promising applications [45][46][47] but they can also allow us to reach a deeper understanding of some of the intriguing phenomena manifested in gel and glassy systems [27,48].…”
Section: Introductionmentioning
confidence: 99%